A Comparision of Access Control Schemes for Cloud Data Privacy - Farooqui, Umar Khalid; Bharti, Ajay Kumar (International Journal of Computer Sciences and Engineering, 2025)
Cloud deliver awesome comfort to its users as the user experience cloud services without having own hardware infrastructure. Now a day’s cloud services have important role on the internet as most of the services used by us are either cloud based or likely to be migrated in to cloud. The open architecture of cloud invites various security and vulnerability issues. The user data are outsourced and there is no strong privacy present between the user and cloud server because cloud uses third party intervention (which generally access the user data and auditing them). Outsourcing cloud data leads various vulnerability and privacy issues. Many researchers proposed different technique to address privacy preservation in the cloud computing, but still they are not 100% succeeded, some of them works on fine grained access control and some advocated attribute base access control scheme. In this paper, we made an attempt to compare two renowned privacy preservation schemes based on Fine Grained and Attribute based access control mechanism